2001
DOI: 10.1080/014461901452058
|View full text |Cite
|
Sign up to set email alerts
|

A study of quantity surveyors' ethical behaviour

Abstract: Several contemporary theories of ethics are reviewed and then linked to professional ethics. A questionnaire survey was conducted to collect primary data regarding quantity surveyors' attitudes towards professional ethics. The subjects were members of the Hong Kong Institute of Surveyors (HKIS). Systematic multivariate statistical analyses, such as ANOVA, F-distribution, and test for significance, were used to draw insight from the survey results. A discrepancy in the standards of professional ethics between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…financial reward) whereas they were less supportive of values such as hedonism, stimulation, tradition, and universalism. These findings were in line with the findings of previous research where the authors found efficiency, financial security, decision making and providence as the values more supported by quantity surveyors (Fan, Ho and Ng, 2001;Alfred, 2007;Bowen et al, 2007). Therefore, quantity surveyors could be defined through their values as those who care about advancement and professional growth.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…financial reward) whereas they were less supportive of values such as hedonism, stimulation, tradition, and universalism. These findings were in line with the findings of previous research where the authors found efficiency, financial security, decision making and providence as the values more supported by quantity surveyors (Fan, Ho and Ng, 2001;Alfred, 2007;Bowen et al, 2007). Therefore, quantity surveyors could be defined through their values as those who care about advancement and professional growth.…”
Section: Discussionsupporting
confidence: 81%
“…But, the literature indicates that there is a lack of knowledge and effective research in terms of the relationship between "profession" variable and personal values. Some studies have focused exclusively on specific professions like IT professionals (Dinger, Thatcher and Stepina, 2010), engineers (Munson and Posner, 1979;Wnek and Williamson, 2010;Koth, 2011;Daniela et al, 2013), R&D professionals (Chang, Choi and Kim, 2008), architects (Bond et al, 2004;Nelson and Shavitt, 2002;Svee, 2014), quantity surveyors (Fan, Ho and Ng, 2001;Alfred, 2007;Bowen et al, 2007) and nurses (Cooman et al, 2008;Hegney, Plank and Parker, 2006). Most of them explained personal values in terms of specific characteristics of the profession and did not generalize their findings beyond that profession.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The population of the study is those quantity surveyors having a membership in the Quantity Surveying Division (QSD) of Hong Kong Institute of Surveyors (HKIS) and practicing in Hong Kong [1]. "Snowball" sampling method was used and the self-administered questionnaires were distributed to quantity surveyors practicing in the five types of organizations, i.e.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Of these operations, earthmoving operations generally represent a major bid item, making their optimization of paramount importance to developing successful bids (Jayawardane and Harris 1990). Acquiring and analysing spatial data has been perceived as a time-consuming process, which is susceptible to certain biases (Fan et al 2001). Several methods have been proposed for accurate estimation of cut quantities (e.g.…”
Section: Introductionmentioning
confidence: 99%